2019
DOI: 10.1186/s12913-019-3871-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Patient Assessment of Chronic Illness Care measure (PACIC-5A) among patients with obesity

Abstract: BackgroundThe Patient Assessment of Chronic Illness Care (PACIC-5A) was developed to assess the satisfaction with patient-provider interaction based on the Chronic Care Model. The additional 5A approach (assess, advise, agree, assist, arrange) allows to score behavioral counseling. The aim of the study was to assess the psychometric properties of the German adaptation of the PACIC-5A questionnaire in a sample of general practitioners (GP) patients with obesity.MethodsAnalyses were based on data from the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This disagreement could affect the patient-provider relationship [20]. Results based on the present INTERACT study suggest that the patient-GP interaction measured with the instrument, "Patient assessment of chronic illness care (PACIC-5A)" is rated as low from patient perspective [18]. However, a good patient-GP relationship and high quality weight consultation are important for patient care [34,35].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This disagreement could affect the patient-provider relationship [20]. Results based on the present INTERACT study suggest that the patient-GP interaction measured with the instrument, "Patient assessment of chronic illness care (PACIC-5A)" is rated as low from patient perspective [18]. However, a good patient-GP relationship and high quality weight consultation are important for patient care [34,35].…”
Section: Discussionmentioning
confidence: 85%
“…Successful weight management is conceptualized as improved overall health and well-being. The design of the INTERACT trial has been reported in detail elsewhere [17,18].…”
Section: Study Design and Samplementioning
confidence: 99%
“…With regards to the patients' experience on conventional chronic disease care, our study shows that the overall PACIC-M mean score among patients with MetS in our primary care setting was satisfactory (2.91 ± 0.04). Previous studies have reported various ranges of PACIC scores depending on the study locality [28][29][30][31]. The variations in PACIC scores observed in different countries may be influenced by the differences in health care delivery system and population background such as socio-economics and cultural factors [28].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant data show the incidence of cancer-related fatigue in colorectal cancer patients can be as high as 80%~95%, which seriously affects the surgical effect and quality of life, requiring professional nursing intervention (16). The 5A nursing by ask, assessment, advice, assistance and access of patients with comprehensive care, adjustment and feedback, better to help improve the ability of self-management, alleviate the pain caused by the operation and the psychological experience, promote the patient recovery at an early date, the nursing mode more attention in patients with diabetes, obesity, less research on colorectal cancer (17,18). In this study, 5A nursing combined with psychological nursing was used for intervention patients undergoing radical resection of colorectal cancer to explore the nursing effect.…”
Section: Comparison Of Overall Nursing Satisfactionmentioning
confidence: 99%